TRAINING LOAD THROUGH HEART RATE AND PERCEIVED EXERTION DURING CROSSFIT® - Dias,Marcelo Ricardo (2022)
ABSTRACT Introduction: Monitoring of CrossFit® training load should be considered to facilitate training outcomes and avoid overtraining. Objective: The purpose of the present study was to examine the heart rate (HR), rating of perceived exertion (RPE), and internal load responses to each segment of a CrossFit® training session. Methods: An observational, cross-sectional design was used in this study. Fifteen healthy male recreational athletes with at least six months experience in CrossFit® training participated in this study. Seven non-consecutive CrossFit® training sessions consisting of mobility, warm-up, skill, and workout segments were performed with a minimum of 48 hours between sessions. Exercise modalities within sessions were constantly varied according to the CrossFit® training programming template. HR was measured every two minutes throughout each session. Peak HR, average HR, RPE after each segment, and session RPE were recorded. Results: HR significantly increased during each segment of the training sessions (p < 0.01), except between the warm-up and skill segments (p = 0.180). Mean total session HR was 65.1 ± 5.4% HRmax and peak HR was 95.3 ± 4.1% HRmax. RPE and internal load increased significantly in each segment (p < 0.05). While intensity measurements increased during CrossFit® training, the HR responses differed from the RPE and internal load. Conclusion: When switching from one segment to another, HR fell below the HRpeak of the previous segment, which shows that the time spent switching between the training segments influenced the average HR of the entire session. Level of evidence III; Case control study; Investigating the results of treatment.